2021
DOI: 10.3389/fneur.2021.742625
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum-Based Calcium Dysfunctions in Synucleinopathies

Abstract: Neuronal calcium dyshomeostasis has been associated to Parkinson's disease (PD) development based on epidemiological studies on users of calcium channel antagonists and clinical trials are currently conducted exploring the hypothesis of increased calcium influx into neuronal cytosol as basic premise. We reported in 2018 an opposite hypothesis based on the demonstration that α-synuclein aggregates stimulate the endoplasmic reticulum (ER) calcium pump SERCA and demonstrated in cell models the existence of an α-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 108 publications
(119 reference statements)
2
11
0
Order By: Relevance
“…It is now generally accepted that the physical contacts between mitochondria and the SR/ER, called mitochondria-associated membranes (MAM), are crucial to Ca 2+ signaling, reactive oxygen species production, autophagy, lipid metabolism, and so on, in various types of cells. Above all, Ca 2+ transfer from the SR/ER to the mitochondria via the inositol-1,4,5 triphosphate receptor (IP 3 R) on the SR/ER, the voltage dependent anion channels (VDACs) on the outer membrane of mitochondria, and the CU mit on the inner membrane of mitochondria, have been well studied (see reviews [ 37 , 38 , 39 , 40 ]). In the heart, the impairment of the Ca 2+ transfer from the SR to the mitochondria via the IP 3 R–VDAC–CU mit axis, which was observed in the mouse model of diabetic cardiomyopathy, disrupted the mitochondrial bioenergetics while the excitation–contraction coupling was unaffected [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is now generally accepted that the physical contacts between mitochondria and the SR/ER, called mitochondria-associated membranes (MAM), are crucial to Ca 2+ signaling, reactive oxygen species production, autophagy, lipid metabolism, and so on, in various types of cells. Above all, Ca 2+ transfer from the SR/ER to the mitochondria via the inositol-1,4,5 triphosphate receptor (IP 3 R) on the SR/ER, the voltage dependent anion channels (VDACs) on the outer membrane of mitochondria, and the CU mit on the inner membrane of mitochondria, have been well studied (see reviews [ 37 , 38 , 39 , 40 ]). In the heart, the impairment of the Ca 2+ transfer from the SR to the mitochondria via the IP 3 R–VDAC–CU mit axis, which was observed in the mouse model of diabetic cardiomyopathy, disrupted the mitochondrial bioenergetics while the excitation–contraction coupling was unaffected [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dot blotting was performed as previously described ( 83 ) where 100 ng of protein was blotted on a nitrocellulose membrane (Hydrobond-C Extra, GE Healthcare). All membranes were blocked in nonfat milk (TBS with 5% nonfat milk, 0.05% Tween 20 and 0.02% sodium azide) for 30 min at RT followed by incubation with primary antibodies overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The most common familial form of PD is caused by mutations in leucine-rich repeat kinase 2 (LRRK2) (Lee et al, 2019;Kovacs et al, 2021). Experiments in astrocytes identified that mutant…”
Section: Mitochondrial Ca 2+ Regulation In Parkinson's Diseasementioning
confidence: 99%
“…The reduced uptake of Ca 2+ into the ER increases ER stress and leads to mitochondrial Ca 2+ overload (Figure 3) (Lee et al, 2019;Kovacs et al, 2021;Modesti et al, 2021). Human fibroblasts from patients with LRRK2 mutations show upregulation of MCU and MICU1, and mitochondria have increased Ca 2+ uptake (Verma et al, 2017;Modesti et al, 2021).…”
Section: Mitochondrial Ca 2+ Regulation In Parkinson's Diseasementioning
confidence: 99%